Utilization of Google Meet Application as Computer Learning Media during COVID-19 Pandemic - Yuri, Jennifer; Crosbie, Kho; Joanna, Charvet (Scientechno: Journal of Science and Technology, 2024)
Learning media is very influential in the teaching and learning process during the COVID-19 pandemic, especially in computer subjects. However, there are still many who have knowledge of existing technology, especially in the use of the Google Meet application in learning media, and to make it easier for teachers to carry out computer learning, it is necessary to use the Google Meet application. The purpose of the study was to determine the benefits of the Google Meet application media on computer learning in high school. This research method uses Quantitative methods with survey models. The survey conducted in this study was online-based using the Google Form Platform. The results of this study explain that learning media using the Google Meet application can be used by teachers and students in helping and improving the teaching and learning process of students in computer courses, especially in high school. The conclusion of this study illustrates that the use of the Google Meet Application is very helpful for teachers and students in the atmosphere of the COVID-19 pandemic. The limitation of this study is that researchers only conducted research on the utilization of the Google Meet Application in Computer subjects, researchers hope that future researchers can conduct the same research but develop it in other subjects.